2018
DOI: 10.3390/molecules23102514
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-MS/MS Method for the Determination of 14 Compounds in Rat Plasma and Its Application in a Pharmacokinetic Study of Orally Administered Xiaoyao Powder

Abstract: Xiaoyao Powder (XYP), a common Chinese medicine, comprises eight traditional Chinese herbs and has been widely used clinically to treat liver damage and mental disorders. An ultra-performance liquid chromatography–tandem mass spectrometry method was developed to investigate the pharmacokinetics of 14 compounds (albiflorin, paeoniflorin, ferulic acid, senkyunolide I, quercetin, isoliquiritigenin, atractylenolide III, ligustilide, atractylenolide II, liquiritin, liquiritigenin, saikosaponin c, glycyrrhizic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The recipe for Xiaoyao Powder was first recorded in "Taiping Huimin Heji Jufang", one of the earlier pharmacopoeia from Song Dynasty in China [23]. In this TCM study, our modified recipe consists of Radix Bupleuri, Radix Angelicae Sinensis, Radix Paeoniae Alba, Rhizoma Atractylodis Macrocephalae, Poria, Rhizoma Zingiberis Recens, Radix Glycyrrhizae Preparata and Herba Menthae in a ratio of 5:5:5:5:5:5:4:1.…”
Section: Drugs and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recipe for Xiaoyao Powder was first recorded in "Taiping Huimin Heji Jufang", one of the earlier pharmacopoeia from Song Dynasty in China [23]. In this TCM study, our modified recipe consists of Radix Bupleuri, Radix Angelicae Sinensis, Radix Paeoniae Alba, Rhizoma Atractylodis Macrocephalae, Poria, Rhizoma Zingiberis Recens, Radix Glycyrrhizae Preparata and Herba Menthae in a ratio of 5:5:5:5:5:5:4:1.…”
Section: Drugs and Reagentsmentioning
confidence: 99%
“…This Xiaoyao Powder solution was subjected to ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS), and 16 common fingerprint peaks were defined and identified. Fourteen target compounds, such as saikosaponin c, albiflorin, paeoniflorin, quercetin, and ferulic acid, were characterized distinctly in the plasma from rats orally administrated the Xiaoyao Powder solution rat as determined by UPLC-MS/MS [23,25]. In this study, chronic hepatic toxicity investigation of a modified recipe solution was carried out by injecting the solution to mice.…”
Section: Licorice Has a Hepatoprotective Role In The Tcm Recipementioning
confidence: 99%
“…In addition, the kidney distribution features between flavonoid glycosides and flavonoid aglycones were different, and the maximum concentration of quercetin was significantly higher than that of other flavonoids. By summarizing the literature (Xu et al, 2018; Zhang et al, 2019), it can be seen that, as flavonoid glycosides, rutin and hyperoside could be hydrolyzed to the corresponding aglycone quercetin in vivo , leading to less absorption in the prototype form. They were also readily metabolized via the liver to form glucuronide and other metabolites after entering the circulation and subsequently eliminated in metabolites via the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 3, we also found that the concentration of flavonoids in many tested tissues increased again after decreasing to a certain extent, which was in accordance with the double peak phenomenon in the plasma concentration–time curves of flavonoid reported previously. The phenomenon may be caused by enterohepatic recirculation, hydrolysis, extensive metabolism and mutual conversion of flavonoids in vivo (Xu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The method was validated in terms of specificity, linearity, lower limit of detection (LLOD), lower limit of quantification (LLOQ), accuracy and precision, extraction recovery, stability, and matrix effects based on the method validation procedure in the previous work [15].…”
Section: Methodsmentioning
confidence: 99%